Application of modified water quality indices as indicators to assess the spatial and temporal trends of water quality in the Dongjiang River. (July 2016) - Sun, Wei; Xia, Chunyu; Xu, Meiying; Guo, Jun; Sun, Guoping
Abstract: The Dongjiang River plays an important role in southern China, as a source for irrigation and potable water of Hongkong and the other parts of the Pearl River Delta (PRD). The water quality index (WQI) was calculated to assess the spatial and temporal variability and identify the classification of water quality in the river. In order to simplify the procedure and reduce the analytical costs of the water quality evaluation, a modified WQI (defined as WQImin ) was introduced based on Principal Component Analysis (PCA) and correlations analyses of the water parameters detected in dry and wet seasons during 2011–2012. Compared with the previous index, similar spatial changing trend and classification of the water quality were obtained by WQImin, which was composed of pH, temperature, total suspended solid, NH4 + -N, and NO3 − -N. The results showed an excellent water quality in the tributary site near the reservoir, a good water quality in the upstream of the river, and medium water quality in the downstream of the river, which suggested that the urban wastewater originated from increasing population size and industry development in the downstream mainly led to the deterioration of water quality along the river. Moreover, WQImin could more adequately reflect the seasonal changes of water quality which was slightly worse in dry season than wet season. Our results also suggest that continuous monitoring should be conducted to prevent pollution from industry and anthropogenic activities.